Isolation, purification and effect of ligands on the nicotinic cholinergic receptor - Kapp, Eugene Anthony (Rhodes University, Faculty of Science, Department of Chemistry and Biochemistry, 1989)
The nicotinic cholinergic receptor protein of the fish electric organ, Torpedo fuscomaculata, has been isolated, purified and shown to represent a true model for the nAChR from other species and higher vertebrates. It is an integral membrane protein composed of four different subunits, tightly associated with other functional, but non-specific proteins. Purification of the nicotinic cholinergic receptor by chromatofocusing demonstrates an improved method over that of affinity and ion-exchange chromatography. Gel chromatography and SDS-polyacrylamide gel electrophoresis show evidence of four subunits; a(40-44 kDa), 6(53 kDa ),'Y(63 kDa) and 6(66 kDa) despite some degradation of receptor molecules by intracellular proteases. Spectrophotometric and fluorimetric studies of receptor-ligand interactions, show the functional and chemical integrity of the receptor to remain intact after solubilisation. The effect of cholinergic ligands on purified receptor preparations indicate quenching of the intrinsic fluorescence of the receptor. Agonists, like acetylcholine, bind and cause local conformational transitions, changing the active region from a hydrophobic to a hydrophilic environment. This phenomenon is illustrated by the 10-fold increase in fluorescence when the receptor is in a desensitised state. Antagonists, such as d-Tubocurarine, block this conformational transition. In vitro rectus abdominis muscle preparations . show the nitrosamines, dimethylnitrosamine and diphenylnitrosamine, to be true agonists of the nAChR. However their low affinity and specificity for the receptor precludes them as photoaffmity labelling agents. Photoactivation of dimethylnitrosamine occurs when associated with an acidic hydrogen at the active site of the receptor, suggesting energy-transfer labelling to be more facile than photoaffmity labelling. The membrane-bound receptor, in the presence of these nitrosamines, undergoes conformational transitions regulating the opening and closing of the ion-channel. Desensitisation and receptor activation are shown to involve one and the same molecular transition.
Keywords: Ligands (Biochemistry); Nicotinic receptors